Detection and characterization of porcine circovirus type 2 (PCV2) circulating in pigs of the departments of Tolima and Huila, Colombia - Almario-Leiva, Geiner (2020)
The aim of this study was to evaluate the presence of the porcine circovirus 2 (PVC2) and the seroreactivity in pig farms in the regions of Tolima and Huila, Colombia, through a cross-sectional study. Blood and tissue samples (lymph nodes, lung and kidney) were taken from animals of all productive stages, including healthy animals and those with signs of the disease. The ELISA test detected seropositive animals in all productive stages. To identify the presence of the virus, the complete ORV2 of PCV2 was amplified by endpoint PCR using DNA extracted from blood, lymph nodes, lung and kidney. The samples were genotyped and finding positive animals for PCV2, both healthy and diseased, at all stages of production. Sequence analysis demonstrated a percentage of identity between 93 and 99% with the PCV2d genotype. Animals without positive clinical signs were positive for the ELISA test and for the PCR, which suggests the presence of subclinical infections or variations in the virulence of the infecting strains. In addition to these tests, an epidemiological survey was conducted, where no significant associations were detected between the presence of the virus and production management.